Quality of judging on the balance beam at the European Championship 2014 - Aleksic-Veljkovic, A.; Herodek, K.; Zivcic-Markovic, K.; Madic, D.; Trajkovic, N. (FIS communications in Physical Education, Sport and Recreation, 2016)
The aim of our research was to analyze the reliability and validity of judges E scores and artistry deductions on the balance beam in the qualifying competition (C I) of the 2014 European Championship in senior (n=89) competition. The following reliability and validity statistics were then calculated: Interclass Correlation Coefficient (ICC), Cronbach' alpha, Kendall coefficient of concordance W and repeated measures ANOVA. All data were analyzed using SPSS 20. The most of the results are satisfying, but correlations between judges for the artistry deductions are smaller than .90 so we can report that the quality of judging artistry was on the lower level comparing to the E score. The results of our investigation showed the need for better definition of the artistry deductions during the next Olympic cycle. Some of the authors suggested that computerized systems for the artistic gymnastics judging should be tested in order to reduce differences between judges.